How is energy poverty linked with citizen perceptions of financial support for low-carbon housing? - Ruokamo, Enni; Karhinen, Santtu; Kemppainen, Teemu; Räihä, Jouni; Strandell, Anna; Marttila, Juhani; Häyrinen, Liina; Toppinen, Anne (Springer Nature, 2026)
Housing affordability and climate sustainability are increasingly interlinked in Europe, as housing costs strain household budgets and the residential sector contributes significantly to greenhouse gas emissions. This study investigates Finnish public perceptions of decarbonization housing policies, particularly views on financial support for the transition to low-carbon housing. Using nationally representative survey data from 2022, combined with housing registry and price data, we analyze how both objective and subjective indicators of energy poverty are linked with support for public funding. The findings demonstrate strong public support, particularly among women, urban residents, and those using oil heating. Objective energy poverty correlates positively with policy support, and subjective economic well-being mediates this relationship. These findings contribute to the growing literature on housing, energy poverty, and climate policy acceptance, underscoring the importance of addressing social vulnerabilities to secure equitable and widely supported low-carbon housing transitions.
Keywords: attitude; energy poverty; household; subsidy; survey